Productive efficiency of wine grape producers in the North of Portugal - Micael Santos; Xosé Antón Rodríguez; Ana Marta-Costa (Wine Economics and Policy, 2021)
Portugal is a country traditionally dedicated to viticulture and characterized by the production of wines of high quality. It has been among the top of 15 countries in the sector in terms of vineyard area extension and wine production, however in recent years Portugal have lost market share in these fields. This situation can be related to the level of productive efficiency of vineyards. Therefore, this study aims to analyse the productive efficiency of wine-growing farms and the determinants that make farms more efficient. The specific hypothesis to be tested is if structural factors of the wine grape farms are determinant of its productive efficiency. To achieve this purpose, we use a database collected by face-to-face surveys from a sample of 154 wine-growing farms with specific input-output information from 2017. These farms are locating in the three regions of the North of Portugal (Minho, Douro and Trás-os-Montes), which represents more than 40% of the Portuguese vineyard area. To analyse the productive efficiency of the farms, we use the Stochastic Frontier Analysis (SFA). The results show that the efficiency level in the wine-growing farms from the North of Portugal is around 68/67%, but with significant differences at regional level. Many of these discrepancies may be due to structural factors, such as the type of wine grapes and the specific characteristics of the region. In conclusion, farms must adjust production management to the existing structural characteristics.
Keywords: 330; technical efficiency; productivity; grape production; stochastic frontier analysis